The Impact of Enhancing Diet Quality or Dietary Supplementation of Flavor and Multi-Enzymes on Primiparous Lactating Sows - Li Zhe; Rui Zhou; Peter Kappel Theil; Uffe Krogh; Lunxiang Yang; Yong Zhuo; Yan Lin; Shengyu Xu; Xuemei Jiang; Lingjie Huang; Lianqiang Che; Bin Feng; et al. (Animals, 2022)
This study was aimed to explore how a high-quality diet or a flavor plus multi-enzyme diet affects the feed intake, nutrient digestibility and antioxidation capacity of lactating sows and the growth of their progeny. Thirty primiparous sows were randomly assigned to three treatments from d 2 of lactation until weaning (d 21): control (CON), with a basal diet; high quality (HQ), with 200 kcal/kg higher net energy than CON; or the CON diet supplemented with 500 mg/kg flavor and 100 mg/kg multi-enzymes (F + E). Sows fed with the HQ or F + E diets improved piglets’ live weight (p < 0.05) and average daily weight gain (p < 0.10), litter weight gain (p < 0.10) and piglet growth to milk yield ratio (p < 0.10). Compared with CON, the HQ and F + E groups increased the digestibility of ether extract, ash, neutral detergent fiber, crude fiber and phosphorus (p < 0.10), and the HQ group also increased dry matter, gross energy, crude protein, acid detergent fiber and energy intake (p < 0.05). Compared with CON, the F + E group decreased serum urea nitrogen and aspartate aminotransferase (p < 0.05) and enhanced superoxide dismutase, catalase and glutathione peroxidase, but it decreased malondialdehyde in milk supernatant (p < 0.05).